Data protection regulation: a comparative law approach - Marcus Abreu de Magalhães (International Journal of Digital Law)
This paper aims to present a comparative approach to data protection regulations around the world. Most countries possess data protection laws in some level of detail. In order to compare structures of data control and compliance in dissimilar systems, the study selected four distinct arrangements : the European General Data Protection Regulation (GDPR); the California Consumer Privacy Act (CCPA); the Brazilian Digital Privacy Law, Lei Geral de Proteção de Dados Pessoais (LGPD); and the Chinese Data Privacy Framework, which is molded by a set of different regulations.